2016
DOI: 10.3233/jad-160369
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II, Randomized, Double-Blind, Placebo-Controlled Study of Safety, Pharmacokinetics, and Biomarker Results of Subcutaneous Bapineuzumab in Patients with mild to moderate Alzheimer’s disease

Abstract: Bapineuzumab SC once-monthly did not demonstrate significant treatment difference over placebo on cerebral amyloid signal at one year but was well-tolerated. There was less ARIA-E than had been expected based on prior experience with comparable exposure on IV bapineuzumab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 11 publications
0
39
0
Order By: Relevance
“…Currently available treatments only target the symptoms of AD, as there are no disease-modifying therapies available for the treatment of AD. New therapeutic approaches include vaccines targeted against Aβ and infusions of antibodies targeting Aβ such as bapineuzumab; however, these approaches have failed in clinical trials to improve clinical outcomes [134] despite being well-tolerated by patients [135,136,137]. While these results were disappointing, there is renewed hope in the clinical effectiveness of aducanumab, an antibody that selectively targets aggregated Aβ which appears to show promise in preclinical studies and clinical trials [138].…”
Section: The Role Of Aging On the Microglial Response To Brain Injmentioning
confidence: 99%
“…Currently available treatments only target the symptoms of AD, as there are no disease-modifying therapies available for the treatment of AD. New therapeutic approaches include vaccines targeted against Aβ and infusions of antibodies targeting Aβ such as bapineuzumab; however, these approaches have failed in clinical trials to improve clinical outcomes [134] despite being well-tolerated by patients [135,136,137]. While these results were disappointing, there is renewed hope in the clinical effectiveness of aducanumab, an antibody that selectively targets aggregated Aβ which appears to show promise in preclinical studies and clinical trials [138].…”
Section: The Role Of Aging On the Microglial Response To Brain Injmentioning
confidence: 99%
“…3,11,15 No dose-related trend was observed for the severity of TEAEs. 16 Furthermore, AAB-003, a humanized antibody derived from bapineuzumab with reduced Fc-receptor-mediated effector function, was developed to reduce the incidence rate of ARIA-E. 17 The PK evaluation of a single SC dose administration of bapineuzumab demonstrated a low volume of distribution, slow clearance, and a prolonged terminal half-life, which were consistent with the kinetics of other IV-administered IgG monoclonal antibodies. 11 Population PK modeling and simulations based on the data from the present study (Janssen Internal Report) demonstrated that mean exposures at steady state (AUC) following the monthly SC doses of 7 mg and 20 mg bapineuzumab were comparable with the observed values following IV doses of 0.15 mg/kg and 0.5 mg/kg every 13 weeks, respectively; however, C max values were much lower.…”
Section: Discussionmentioning
confidence: 71%
“…A subsequent phase 2a study confirmed that the incidence of ARIA-E was lower following monthly SC administrations of 7 and 20 mg bapineuzumab compared with their equivalent IV dose groups, suggesting a safety advantage with SC administration. 16 Furthermore, AAB-003, a humanized antibody derived from bapineuzumab with reduced Fc-receptor-mediated effector function, was developed to reduce the incidence rate of ARIA-E. 17 The PK evaluation of a single SC dose administration of bapineuzumab demonstrated a low volume of distribution, slow clearance, and a prolonged terminal half-life, which were consistent with the kinetics of other IV-administered IgG monoclonal antibodies. 18 The PD assay measured only total plasma Aβ x-40 .…”
Section: Discussionmentioning
confidence: 71%
“…Bapineuzumab, a fully humanized immunoglobulin G1 IgG1N-terminal-specific anti-Aβ monoclonal antibody (Kerchner & Boxer, 2010;Salloway et al, 2014), was evaluated in several phase II and III studies investigating efficacy on clinical and biomarker outcome measures in participants with mild-to-moderate AD (Blennow et al, 2012;Brody et al, 2016;Rinne et al, 2010;Salloway et al, 2009Salloway et al, , 2014 (Siemers et al, 2016). Results of these secondary analyses served as the basis for EXPEDITION 3, a phase III placebo-controlled, double-blind study in participants with mild AD who were amyloid-positive by florbetapir positron emission tomography (PET) or by CSF Aβ(1-42) measurements (Honig et al, 2018).…”
Section: Rofecoxibmentioning
confidence: 99%